The phylogeny of Empis and Rhamphomyia (Diptera, Empididae) investigated using UCEs including an over 150 years old museum specimen - Caroline Rhodén; Emma Wahlberg (Evolutionary Systematics, 2020)
The genera Empis Linneus, 1758 and Rhamphomyia Meigen, 1822 (Empidoidea, Empididae Latreille, 1809) are two large genera of flies commonly named dagger flies. They are widely distributed in the world with most species described from the Palearctic Region. Empis comprises about 810 described species and Rhamphomyia comprises about 610 described species, together they represent one third of the known species diversity in Empididae. Two recent studies on the phylogeny of the two genera using Sanger sequencing on a few genetic markers, did not support monophyly of them. In this study high throughput sequencing of target enriched molecular data of ultraconserved elements or UCEs was used to investigate the phylogenetic relationships of included representatives of the genera. This method has proven useful on old and dry museum specimens with high amounts of degraded DNA, which was also tested herein. For this purpose, a commercially synthesized bait kit has previously been developed for Diptera which this study was the first one to test. Three out of nine old and dry museum specimens were successfully sequenced, one with an age of at least 154 years. Higher DNA concentration yielded a greater number of reads. Analyses conducted in the study confirmed that both Empis and Rhamphomyia are non-monophyletic.